FACTORS OF NONSPECIFIC RESISTANCE OF CALVES IN DAIRY CATTLE BREEDING - Semenov Vladimir Grigoryevich; Baimukanov Dastanbek Asylbekovich; Alentayev Aleidar Saldarovich; Kirillov Nikolay Kirillovich; Karynbayev Amanbai Kambarbekovich; Aldyakov Alexey Vladimirovich (Scientific Journal of Pedagogy and Economics, 2021)
Under the influence of the biostimulant, an increase in the morphological and biochemical data of blood in calves grown both on private plots and on small and medium farms, which at the end of the observation period exceeded the control values: the number of red blood cells - by 0.98; 0.81 and 0.79x1012/l, hemoglobin - by 9.8; 7.0 and 6.2 g/l, albumins - by 2.2; 2.8 and 3.5 g/l, γ-globulins - by 5.5; 3.7 and 5.6 g/l (P <0.05-0.001), respectively. The data on the leukocyte phagocytic activity, plasma lysozyme activity, serum bactericidal activity, and immunoglobulins were higher than in the control: when rearing calves in private subsidiary plots - by 5.6%, 4.8%, 5.5% and 4.7 mg/ml, on a small farm - by 5.2; 4.2; 7.8 % and 3.6 mg/ml and on a medium farm - by 5.8%, 3.6%, 4.4% and 4.3 mg/ml, respectively (P<0.05-0.01). A rising in the technological stress on the calf’s organism was revealed depending on the increase in the enterprise capacity, which is confirmed by the bioamine blood spectrum.